Corporate Governance Spillover through Bootstrapping and ASEAN Bidder CBMA Success - Nurhazrina Mat Rahim; Ruhani Ali; Ei Yet Chu (Asian Academy of Management Journal of Accounting and Finance, 2021)
This study aims to examine whether the difference in country-level corporate governance between ASEAN bidding and the target country could explain the performance change (Tobin’s Q) following a Cross-border merger and acquisition (CBMA); hence, the CBMA success. Using 142 CBMAs involving ASEAN firms as the bidder over the period 2002 to 2013, the study found that the difference in country-level corporate governance could result in corporate governance spillover through bootstrapping. This has resulted in the improvement of ASEAN bidder corporate governance and positively affected the CBMA success. However, the improvement must be large enough to outweigh the high acquisition cost.